The influence of paternal engagement on the quality of life of mothers of children with disabilities - Paranhos, Julie Stephanny de Souza Gurgel; Vidigal, Gabriela Muniz dos Santos; Takeshita, Isabela Mie; Hudson, Gabriela dos Reis Vieira; Hudson, Rodrigo Vieira; Silveira, Carla de Paula (Saúde e Sociedade, 2024)
The literature often describes the burden experienced by mothers as one of the main challenges faced by families with children with disabilities, which can lead to mental health problems. Little is found about the participation of fathers and how this participation impacts the quality of life of mothers. The objective is to investigate the correlation between paternal engagement and the quality of life of mothers of children with disabilities. This is a cross-sectional, descriptive, quantitative and qualitative study, carried out with fathers and mothers of children with disabilities undergoing treatment at a neurofunctional rehabilitation clinic. It was found, based on the responses of 35 fathers and 35 mothers, that there is no linear correlation between the variables surveyed, however most mothers want more help to take care of their children and would like fathers to be more involved in their treatment. The engagement of parents of children with disabilities was similar to that of parents of typical children, being more linked to emotional support than direct and indirect care. It is concluded that studies like this are necessary in populations with different characteristics, to verify the behavior of the variables; and qualitative approaches with parents are needed.